Citizens’ attitudes towards institutional change in contexts of political turbulence: support for regional decentralisation in Ukraine - Chaisty, P; Whitefield, S (SAGE Publications, 2017)
Most studies of public opinion regarding constitutional change focus on ‘winners’ and ‘losers’ in established democracies, but in comparative terms most institutional change takes place in unstable political contexts. We contend that mass preferences towards institutional choices are likely to differ significantly in turbulent contexts as compared to stable polities. In this article, we consider the issue of public preferences towards proposals for regional decentralisation in the context of post-Soviet Ukraine, a society that has been in the throes of political uncertainty for the last decade. Using surveys conducted in war-torn Ukraine in 2014, we find that under conditions of political uncertainty the institutional preferences of citizens are connected to group identities and ideological orientations rather than instrumental concerns.